2016
DOI: 10.2166/washdev.2016.034
|View full text |Cite
|
Sign up to set email alerts
|

Looking beyond headline indicators: water and sanitation services in small towns in Ethiopia

Abstract: This paper presents findings on water and sanitation service levels from 16 small and medium towns in four regions of Ethiopia. In these settlements, the proportion of people with access to improved water and sanitation services is found to be high and consistent with other major datasets and reports for urban Ethiopia. However, when service characteristics such as reliability, quality, quantity and accessibility (including travel and queuing time) of water are considered, and for sanitation, quality and use, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…According to WHO/UNICEF's Joint Monitoring Programme (JMP), access to improved water services in urban areas in Ethiopia has improved from 84% in 1990 to 93% in 2015 and access to piped water on premises also increased considerably, from 10% to 56% during the same time period (WHO/UNICEF, 2017). However, these largely positive coverage figures hide the reality of low levels of service and challenges related to the sustainable provision of small town water services (Adank et al, 2016).…”
Section: Setting the Scene: Small Town Water Services Provision In Etmentioning
confidence: 99%
See 1 more Smart Citation
“…According to WHO/UNICEF's Joint Monitoring Programme (JMP), access to improved water services in urban areas in Ethiopia has improved from 84% in 1990 to 93% in 2015 and access to piped water on premises also increased considerably, from 10% to 56% during the same time period (WHO/UNICEF, 2017). However, these largely positive coverage figures hide the reality of low levels of service and challenges related to the sustainable provision of small town water services (Adank et al, 2016).…”
Section: Setting the Scene: Small Town Water Services Provision In Etmentioning
confidence: 99%
“…Data were collected by enumerators using surveys loaded on phones using Akvo FLOW software. Further methodological details on collection of service level data are included in Adank et al (2016).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Apart from socio-economic factors, other factors like availability of clean water, the survival of the environmental stages of the parasites, personal and public hygiene practices play a central role in the transmission of intestinal parasites [9,10]. Ethiopia has one of the bottommost clean water supply and latrine coverage [11]. Studies carried out in Ethiopia indicated that personal hygienic factors like hand washing after toilet use, medical cheek up including stool examinations, and knowledge about intestinal parasites contribute to the prevalence of intestinal parasite infections among food handlers of food service establishments [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Excluding data that indicates no response and don't know. 2 Other service providers of n = 20,438: Owner/Private household (n = 78, 0.38%), Private contractor or operator (n = 59, 0.29%), WUA (n = 17, 0.08%), NGO (n = 9, 0.04%), Local Government (n = 8, 0.04%), Public operator/utilities (n = 6, 0.03%). 3 Includes both WPC and Area Mechanic, n = 1315 (66.82%).…”
mentioning
confidence: 99%
“…Excluding data that indicates no response and don't know 2. Responses include either "Affordability" or "Maintenance" as a consideration, with the exception of n = 2 occurrences in "=2" category.…”
mentioning
confidence: 99%